Evaluation of aortic 18F-NaF tracer uptake using PET/CT as a predictor of aortic calcification in postmenopausal women: A longitudinal study. (May 2019) - Cecelja, Marina; Moore, Amelia; Fogelman, Ignac; Frost, Michelle L; Blake, Glen M; Chowienczyk, Phil
Introduction: Aortic calcification as detected by computed tomography is associated with arterial stiffening and is an important predictor of cardiovascular morbidity and mortality. Uptake of 18 F-sodium fluoride ( 18 F-NaF) in the aortic wall reflects metabolically active areas of calcification. The aim of this study was to determine if 18 F-NaF uptake in the aorta is associated with calcification and progression of calcification as detected by computed tomography. Methods: Twenty-one postmenopausal women (mean age 62 ± 6 years) underwent assessment of aortic 18 F-NaF uptake using positron emission tomography/computer tomography at baseline and a repeat computed tomography scan after a mean follow-up of 3.8 ± 1.3 years. Tracer uptake was quantified by calculating the target-to-background (TBR) ratios at baseline and follow-up. Calcification was assessed at baseline and follow-up using computed tomography. Results: Over the follow-up period, aortic calcium volume increased from 0.46 ± 0.62 to 0.71 ± 0.93 cm 3 ( P < 0.05). However, the change in calcium volume did not correlate with baseline TBR either unadjusted ( r = 0.00, P = 1.00) or adjusted for age and baseline calcium volume (beta coefficient = −0.18, P = 0.42). TBR at baseline did not differ between participants with ( n = 16) compared to those without ( n = 5) progression in calcium volume (2.43 ± 0.46 vs. 2.31 ± 0.38, P = 0.58). In aortic segments identified to have the highest tracer uptake at baseline, calcium volume did not significantly change over the follow-up period ( P = 0.41). Conclusion: In a cohort of postmenopausal women, 18 F-NaF uptake as measured by TBR in the lumbar aorta did not predict progression of aortic calcification as detected by computed tomography over a four-year follow-up.